Mutation in pre-mRNA adenosine deaminase markedly attenuates neuronal tolerance to O(2) deprivation in Drosophila melanogaster - Ma, Enbo (American Society for Clinical Investigation, 2001)
O(2) deprivation can produce many devastating clinical conditions such as myocardial infarct and stroke. The molecular mechanisms underlying the inherent tissue susceptibility or tolerance to O(2) lack are, however, not well defined. Since the fruit fly, Drosophila melanogaster, is extraordinarily tolerant to O(2) deprivation, we have performed a genetic screen in the Drosophila to search for loss-of-function mutants that are sensitive to low O(2). Here we report on the genetic and molecular characterization of one of the genes identified from this screen, named hypnos-2. This gene encodes a Drosophila pre-mRNA adenosine deaminase (dADAR) and is expressed almost exclusively in the adult central nervous system. Disruption of the dADAR gene results in totally unedited sodium (Para), calcium (Dmca1A), and chloride (DrosGluCl-α) channels, a very prolonged recovery from anoxic stupor, a vulnerability to heat shock and increased O(2) demands, and neuronal degeneration in aged flies. These data clearly demonstrate that, through the editing of ion channels as targets, dADAR, for which there are mammalian homologues, is essential for adaptation to altered environmental stresses such as O(2) deprivation and for the prevention of premature neuronal degeneration.